PERHITUNGAN JUMLAH SEL CD4 DENGAN SEROPOSITIF IgM HERPES SIMPLEKS TIPE-2 DI PASIEN HIV - Bastiana Bermawi; Endang Retnowati K; Erwin A Triyono (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2009)
Herpes simplex type-2 (HSV-2) infection is usually transmitted sexually and can cause recurrent, painful genital ulcers. Seropositivityof IgM HSV-2 indicates acute infection of HSV-2. The low level of CD4 cell counts can lead to opportunistic infection in HIV patients.Therefore, the aim of this study is to investigate the association between CD4 cell counts and HSV-2 infection (based on seropositivity ofIgM HSV-2) in HIV patients with heterosexual risk factor in Dr. Soetomo Hospital, Surabaya. Specimens were collected during the firstpresentation on June and July 2008. HSV-2 IgM and was assessed by an ELISA technique using Herpelisa 2 IgM (recombinant) reagent,whereas CD4 cell counts was assessed by a Flowcytometry BD FACSCaliburTM System. The seropositivity of IgM HSV-2 in HIV persons18 years of age or older was 27.3% (9/33). Median CD4 cell counts the number were 50 cells in μl. Persons with seropositive HSV-2who had CD4 cell counts < 200 cells/μL and > 200 cells/μL were 66.6% (6/9) and 33.3% (3/9), respectively. Using chi square test,there was no association between CD4 cell counts and seropositivity of IgM HSV-2 in HIV patients. The seropositivity of IgM HSV-2 inHIV patients with heterosexual risk factor in Dr. Soetomo Hospital was 27.3%. There was no association between CD4 cell counts andthe seropositivity of IgM HSV-2 in HIV patients with heterosexual risk factor.